Pelatihan dan Pendampingan Organisasi Siswa Madrasah untuk Menumbuhkan Jiwa Kepemimpinan di MAS YPI Batang Kuis - Arbaatun, Arbaatun; Harahap, Rizky Afriyanti; Hotimah, Fatimatu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
This study aims to examine the implementation of Student Leadership Basic Training at MAS YPI Batang Kuis, focusing on the effectiveness of the methods used to instill leadership attitudes in students. Changes in approach and the implementation of democratic leadership styles are crucial aspects under evaluation. The research method employed is a descriptive case study with a qualitative approach. Data were collected through observations, interviews, and document analysis related to the implementation of LDKS in the school. Data collection occurred during the LDKS implementation period and some time thereafter. The results of the study indicate that the one-month implementation of LDKS at MAS YPI Batang Kuis successfully instilled leadership attitudes in students with a democratic approach. Periodic evaluations, the establishment of the Intra-Madrasa Student Organization (OSIM), and changes in content and approach were determining factors for success. Positive attitudes, discipline, responsibility, and communication skills appear internalized in the day-to-day activities of the OSIM officials. Based on the research findings, it is recommended that schools conducting LDKS consider the application of democratic leadership styles in teaching and evaluation. Involving students in decision-making processes, improving communication, and assigning responsibilities can be effective steps in shaping sustainable leadership attitudes.